Medialne reprezentacje (auto)biografii na przykładzie spektakli teatralnych Michała Buszewicza i Weroniki Szczawińskiej - Beata Popczyk-Szczęsna (Zagadnienia Rodzajów Literackich)
This article seeks to examine (auto)biographical plays. Texts and performances inspired by biographical material form a significant part of contemporary dramaturgy and theatrical projects. In Poland, this type of activity is the domain of directors coming from different generations and representing various styles, for example, Krystian Lupa, Maciej Wojtyszko, Wiktor Rubin, Michał Buszewicz, Weronika Szczawińska. Both dramatic texts and stage performances inspired by (auto)biography are non-uniform messages with updates of various genre forms. They may thus be classified as “blurred genres.” Two plays (An Autobiography Just in Case by Michał Buszewicz and Simply by Weronika Szczawińska) shown online during the Divine Comedy theatrical festival in Krakow in 2020 were used to analyze the diverse genre features of stage statements (characteristic of, among other things, intimate journal, autobiography, performance or theatre of fact) and the phenomenon of media mediation of theatrical performances made available to the audience via the streaming platform. The form of the theatrical texts is of great importance in the staging process. Regardless of whether they are autonomous dramatic texts that exist prior to their performance or scripts written specifically for the needs of a given theater project, their dramatic model contributes substantially to the aesthetics of the spectacle. In specific stage productions, these texts — due to their performative properties — combine other stage matter in a coherent manner, thus creating an important tool for representing (auto)biography and an instrument for engaging the audience.